2021
DOI: 10.1200/go.20.00538
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcomes of Breast Cancer in Sudanese Women: A Hospital-Based Study

Abstract: PURPOSE Breast cancer (BC) is the leading malignancy among Sudanese women. Yet, data on survival are limited. This study aimed to determine 5-year overall survival (OS) of BC in Sudanese women, and identify prognostic demographic and clinicopathologic factors. PATIENTS AND METHODS A hospital-based retrospective study was conducted by reviewing data of women with BC diagnosed and treated at the National Cancer Institute—University of Gezira during 2012, and followed up to end of August 2018. Data were retrieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…In this study, the mean age of patients was 50 ± 11.7 years. This finding is in line with previous studies which reported that most BC patients were above 45 or 50 years old, and the disease frequently occurs in women around menopause [27][28][29][30][31]. However, BC can strike at any age; and 4% of cases occur in women under 40 years old [32].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the mean age of patients was 50 ± 11.7 years. This finding is in line with previous studies which reported that most BC patients were above 45 or 50 years old, and the disease frequently occurs in women around menopause [27][28][29][30][31]. However, BC can strike at any age; and 4% of cases occur in women under 40 years old [32].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the mean age of patients was 50 ± 11.7 years. This nding is in line with previous studies which reported that most breast cancer patients were above 45 or 50 years old, and breast cancer frequently occurs in women around menopause [29][30][31][32][33]. However, breast cancer can strike at any age; and 4% of breast cancer cases occur in women under 40 years old [34].…”
Section: Discussionsupporting
confidence: 91%
“…In Sudan, the majority of cancer patients have locally advanced or metastatic disease at presentation [ 8 13 ]. Currently available data from Sudan suggest that 90% of the terminally ill cancer patients suffered from uncontrolled pain [ 14 ].…”
Section: Discussionmentioning
confidence: 99%